Upaya Meningkatkan Hasil Belajar Matematika Melalui Latihan Terbimbing di Kelas XII IPS 2 SMAN 1 Candung Tahun Pelajaran 2018/2019 - Nilafatma Nilafatma (Journal on Education, 2022)
This research started from the problem of the low learning outcomes of mathematics in class XII IPS 2 at SMAN 1 Candung. This study aims to determine student learning outcomes in mathematics by using the guided practice learning model. This research is classified as classroom action research. The research was conducted in class XII IPS 2 of SMAN 1 Candung with 20 students. The research procedure is in two cycles. Each cycle consists of two meetings in which each meeting contains planning, action, observation, and reflection. Data collection techniques with observation, documentation, and tests. Data analysis carried out in this study is reduction, data presentation and conclusion drawing. The guided practice learning model can make it easier for students to understand the material presented by the teacher. The results of this study indicate that the use of the guided practice learning model can improve mathematics learning outcomes in class XII IPS SMA N 1 Candung.